2019
DOI: 10.1177/2325967119842881
|View full text |Cite
|
Sign up to set email alerts
|

Does Medial-Row Fixation Technique Affect the Retear Rate and Functional Outcomes After Double-Row Transosseous-Equivalent Rotator Cuff Repair?

Abstract: Background: Double-row transosseous-equivalent (TOE) rotator cuff repair techniques have been widely accepted because of their superior biomechanical properties when compared with arthroscopic single-row repair. Concerns regarding repair overtensioning with medial-row knot tying have led to increased interest in knotless repair techniques; however, there is a paucity of clinical data to guide the choice of technique. Hypothesis: Arthroscopic TOE repair techniques using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…In our study, preoperative LMR was not related to postoperative retear. Previous systematic reviews have found that for nonmassive RCTs, the retear rate averaged approximately 20% 13 and ranged from 0% to 48%. 25 Regarding the retear rate for small to large RCTs, Kim et al 29 reported 0% at a mean follow-up of 21.9 months, and Mihata et al 41 reported a range of 3.5% to 9.1% at 2 years after RCT.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, preoperative LMR was not related to postoperative retear. Previous systematic reviews have found that for nonmassive RCTs, the retear rate averaged approximately 20% 13 and ranged from 0% to 48%. 25 Regarding the retear rate for small to large RCTs, Kim et al 29 reported 0% at a mean follow-up of 21.9 months, and Mihata et al 41 reported a range of 3.5% to 9.1% at 2 years after RCT.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Consequently, better tendon healing after TOE repairs has been observed in a sheep model when compared with healing after SR and DR repairs. 35 As a result of these findings and due to their excellent clinical results, 12,30,34 TOE repair techniques are now preferred by many surgeons. 11,36,40 Nevertheless, TOE as well as DR repairs can lead to a more severe failure mode with retear of the rotator cuff not at its insertion site on the greater tuberosity but medial to it at the level of the medial row anchors or the musculotendinous junction.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, a retrospective study by Burns et al 10 found that knotted technique for rotator cuff repair required more surgical time than knotless technique, and in another study, Elbuluk et al 11 found that the rate of tendon failure in knotted repair could be the cause of failed rotator cuff repair. However, Sheean et al 12 suggested that the authors of some studies need to be cautious when interpreting results regarding failure of the knotted technique because of the variety of techniques of knot-tying.…”
Section: Suture Tension In Double-row Suture-bridgementioning
confidence: 98%